Investigating the expression of the CRISPR-associated Cas genes in Mycobacterium tuberculosis under antibiotic stress - Cook, Emma Nancy (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.